2014
DOI: 10.1016/j.juro.2014.06.084
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trial of Intravesical Nanoparticle Albumin Bound Paclitaxel for the Treatment of Nonmuscle Invasive Urothelial Carcinoma of the Bladder after bacillus Calmette-Guérin Treatment Failure

Abstract: Intravesical nab-paclitaxel has minimal toxicity and a 35.7% response rate in patients with nonmuscle invasive bladder cancer and previous bacillus Calmette-Guérin failure. Complete response remained durable at 1 year followup in this heavily pretreated patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 26 publications
0
41
0
3
Order By: Relevance
“…Furthermore, a recent study including 40 patients with BCG refractory or relapsing disease with a primary end point as recurrence-free survival revealed that 35% (14/40) of the patients remained free of HG recurrence at 12 months after the initiation of the treatment. [64] Of 11 patients with long-term (3 years) data, 8 remained free of disease during a period ranging between 15 and ≥36 months. Ninety-seven percent of the patients experienced adverse events, for majority (78%) of them adverse events were transient and classified as either grade 1 or 2.…”
Section: Future Conceptsmentioning
confidence: 99%
“…Furthermore, a recent study including 40 patients with BCG refractory or relapsing disease with a primary end point as recurrence-free survival revealed that 35% (14/40) of the patients remained free of HG recurrence at 12 months after the initiation of the treatment. [64] Of 11 patients with long-term (3 years) data, 8 remained free of disease during a period ranging between 15 and ≥36 months. Ninety-seven percent of the patients experienced adverse events, for majority (78%) of them adverse events were transient and classified as either grade 1 or 2.…”
Section: Future Conceptsmentioning
confidence: 99%
“…9 Results of the phase 2 data were recently reported. 10 A complete response was observed in 10 (35.7%) of 28 patients treated with NAB-paclitaxel with recurrent NMIBC who had failed at least 1 prior BCG regimen. 10 In murine models, the mTOR inhibitor rapamycin was found to potentiate the induction of BCGmediated immune responses in mice.…”
Section: Nanoparticle-based Therapymentioning
confidence: 95%
“…10 A complete response was observed in 10 (35.7%) of 28 patients treated with NAB-paclitaxel with recurrent NMIBC who had failed at least 1 prior BCG regimen. 10 In murine models, the mTOR inhibitor rapamycin was found to potentiate the induction of BCGmediated immune responses in mice. 11 In addition, rapamycin demonstrated antitumor activity in preclinical models of bladder cancer.…”
Section: Nanoparticle-based Therapymentioning
confidence: 95%
“…In this phase II study by McKiernan et al (page 1633) from New York the maximum deliverable dose of nab-paclitaxel was given to 28 patients after BCG failed to treat urothelial carcinoma of the bladder. 6 Nab-paclitaxel has a fivefold higher solubility compared to docetaxel, facilitating drug delivery into tumor cells via albumin receptor mediated transport across epithelial cells.…”
Section: Phase II Trial Of Intravesical Nab-paclitaxel For Nonmuscle mentioning
confidence: 99%